2018
DOI: 10.1098/rsos.171082
|View full text |Cite
|
Sign up to set email alerts
|

Frequency doubling by activein vivomotility of mechanosensory neurons in the mosquito ear

Abstract: Across vertebrate and invertebrate species, nonlinear active mechanisms are employed to increase the sensitivity and acuity of hearing. In mosquitoes, the antennal hearing organs are known to use active force feedback to enhance auditory acuity to female generated sounds. This sophisticated form of signal processing involves active nonlinear events that are proposed to rely on the motile properties of mechanoreceptor neurons. The fundamental physical mechanism for active auditory mechanics is theorized to rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…[41], in that the prongs act more or less as rigid-body extensions of the flagellum. Possible variations inside the pedicel would likely be due to the scolopidia, which have recently been shown, by direct measurement using atomic force microscopy, to be motile [42], having long been suspected as the source of stiffness gating. Further studies have shown the importance of the scolopidia for both power gain of the antenna, and the intra- and interspecifc variations seen in antennal mechanics [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41], in that the prongs act more or less as rigid-body extensions of the flagellum. Possible variations inside the pedicel would likely be due to the scolopidia, which have recently been shown, by direct measurement using atomic force microscopy, to be motile [42], having long been suspected as the source of stiffness gating. Further studies have shown the importance of the scolopidia for both power gain of the antenna, and the intra- and interspecifc variations seen in antennal mechanics [32].…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Avitabile et al [41], in that the prongs act more or less as rigid-body extensions of the flagellum. Possible variations inside the pedicel would likely be due to the scolopidia, which have recently been shown, by direct measurement using atomic force microscopy, to be motile [42], having long been suspected as the source of stiffness royalsocietypublishing.org/journal/rsif J. R. Soc. Interface 16: 20190049 gating.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%
“…Interestingly, neurons from peripheral nervous systems show higher resistance to mechanical damage than neurons from the brain 99 , providing insight into how neurons may cope with mechanical trauma. Other recent advances include the use of optical microscopy to guide the atomic force microscope probe to mechanically stimulate cellular systems involved in the hearing of mice or insects and to characterize their functional response [100][101][102] , leading to the observation that the response of mechanosensory neurons of the hearing organ to mechanical stimulation is nonlinear 102 .…”
Section: Case Studiesmentioning
confidence: 99%
“…1, H1-H3). Apart from having an olfactory function, antennae also mediate sound detection in mosquitoes (e.g., Warren et al 2010;Lapshin 2012;Windmill et al 2018;Su et al 2018) and the evolution of overall antennal morphology has most likely been driven by demands of both olfaction and hearing.…”
Section: Olfactory Organsmentioning
confidence: 99%